Dampak Pandemi Covid-19 Terhadap Stabilitas Profit Efficiency Perbankan Syariah Indonesia - Ahmad - Rivai; Syachrul Wahyudi; M. Shabri Abd. Majid; Marliyah Marliyah; Rita Handayani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This research aims to investigate the impact of the COVID-19 pandemic on the stability of profit efficiency in Indonesian Islamic banking. The analysis used is quantitative by using Stochastic Frontier Analysis (SFA) as a method for estimating the profit efficiency of Islamic Commercial Banks (BUS) and Sharia Business Units (UUS) before and during the COVID-19 pandemic. The data used is secondary data for BUS and UUS in the period January 2018 to August 2021. From this research it was found that the overall phenomenon of Indonesian Islamic banking has a higher level of profit efficiency during the COVID-19 pandemic than before the pandemic. Partially, UUS has a higher level of profit efficiency than BUS before and during the COVID-19 pandemic. In terms of stability, it also shows the same phenomenon, UUS has higher stability than BUS in generating profits both before and during the COVID-19 pandemic. In this study, it was also found that Total deposit and Non-Performing Financing act as significant determinant factors for the stability of profit efficiency of BUS and UUS. The results of this study further strengthen the existence of Indonesian Islamic banking in the future in facing times of economic and financial crisis